التنشئة الجتماعية في الأسرة وتمثل الدور لدى الفتاة د ا رسة ميدانية على عينة من الطالبات بجامعة زيان عاشور الجلفة - لجلط فاطمة أحلام (université M'sila, 2022)
The study aims to determine whether there are differences between the nature of the role that a girl is raised in as a university student based on actual family socialization and her representation of that role while revealing her direction. The study used the descriptive approach based on qualitative and quantitative analyzes. It was conducted on two samples (300) female students using the questionnaire tool and (10) female students using the interview tool. According to the study, the university girl represents a social center and a role in education, and education is more important than what is prevalent in actual family socialization. In her family, a lesser role is represented in terms of domestic affairs, while the same sexual role and the role associated with chastity and modesty are actually represented.